Comprehensive Tracer Study of San Sebastian College-Recoletos Manila (2018-2023) - Maranan, Mario; Competente, Francis; Carabeo, Anton Maria Francesco; Viernes, Ferlie Rose (JPAIR Institutional Research, 2024)
The employability of graduates from San Sebastian College Recoletos (SSCR) between 2018 and 2023 is under scrutiny in the Comprehensive Tracer Study, which also delves into the impact of their education on their ability to thrive in the realm. This research aims to analyze the employment status and demographic characteristics of these graduates, evaluate their perspectives on job-hunting practices, and assess how effectively their education equipped them for the working world. A total of 440 graduates participated in a research project by completing a self-designed survey tool via a platform. In order to uncover patterns and connections within the data set, we carried out an analysis utilizing weighted calculations alongside examining the frequency distributions and conducting an Analysis of Variance (ANOVA). The outcomes indicate that most graduates achieve job placements, with a proportion securing positions shortly following graduation. The research underscores the importance of workshops and conferences in enhancing job prospects, particularly for individuals who land jobs within a year post-graduation. Considering everything, the research showcases the effectiveness of SSCR initiatives in facilitating graduates’ transition into the job market and identifies areas where enhanced graduate tracking and support services are needed. This analysis could assist SSCR in enhancing its strategies for equipping students with the skills, for employment success.